ANALISIS SEGMENTASI PENONTON BIOSKOP YOGYAKARTA - Suwarto, Dyna Herlina (Informasi, 2016)
After the long period of the cinema industry decline, the number of audience who visit cinema increases significantly. However, the research to examine the phenomena of audience segmentation is very few. Therefore the study aim is to investigate cinema audience segmentation in Yogyakarta on the basis of the aspects that affects the audience film choice. Furthermore the mix-method approach combining qualitative and quantitative method in sequence was employed to attain the research objective. For the first step, three focus group discussions that involve 20 informants. The second step, survey was conducted involving 454 respondents. The result indicates that there are two different audience segments according their behaviors. The first segment visits the cinema as fun activities in their spare time meanwhile the second segment considers the activity as a cultural interest in order to enjoy the narrative and artistic aspects of a film